FITRAT IS ABOUT CITY MANAGEMENT - Sanobar Karimova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the 1930s, when the period of independence was full of horrors, he returned a group of Uzbek intellectuals who were innocently shot, lost, and exiled to their people. The creations of "enemies of the people" such as Cholpon, Fitrat, and Elbek broke the strong fences placed in dark rooms and became people’s favorite works.